The human in model‐driven engineering loop: A case study on integrating handwritten code in model‐driven engineering repositories. (18th February 2021) - Rahad, Khandoker; Badreddin, Omar; Mohsin Reza, Sayed
Abstract: In model‐driven engineering (MDE) software projects, large portions of the executable code are automatically generated from designs and models. This generated code may or may not be edited by the developers to achieve their development objectives. MDE projects also include a significant amount of handwritten code (HC). This handwritten code is developed under unique constraints, as it must integrate with generated artifacts and code elements that are not directly developed by the engineers. These constraints adversely affect codebase quality and maintainability. This case study aims to investigate the hypothesis pertaining to the handwritten code quality developed in the context of MDE. The study analyzes these unique code fragments and compares their characteristics to handwritten code in repositories where code generation is not present. The study finds that handwritten code quality in the MDE context suffers from elevated technical debt and code smells. We observe key code smells that are particularly evident in this handwritten code. These findings imply that code generators must optimize for human comprehension, prioritize extensibility, and must facilitate integration with handwritten code elements.